1986
DOI: 10.1055/s-0038-1661553
|View full text |Cite
|
Sign up to set email alerts
|

An IgM Lupus Anticoagulant that Neutralizes the Enhancing Effect of Phospholipid on Purified Endothelial Thrombomodulin Activity-A Mechanism for Thrombosis

Abstract: SummaryAn anticoagulant activity was isolated from the plasma of a patient with a strong lupus-like anticoagulant using gel filtration by high performance liquid chromatography. IgM were detected in this anticoagulant fraction which exhibited specificity towards 50% phosphatidylcholine - 50% phosphatidylserine vesicles and cardiolipin. These phospholipids were able to produce an apparent 3-fold enhancement of purified human protein C activation by human a-thrombin in the presence of purified human placenta thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
1
1

Year Published

1987
1987
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(55 citation statements)
references
References 10 publications
1
52
1
1
Order By: Relevance
“…In these latter studies it was emphasized that the 4-carboxyglutamic acid domain was essential for activation by the thrombin-thrombomodulin complex, suggesting that interaction of the substrate with membrane is an essential prerequisite of the activation process. This was corroborated by the observation that an IgM lupus anticoagulant, with specificity directed towards anionic phospholipids, was able to neutralize the enhancing effect of phospholipids on purified thrombomodulin activity (Freyssinet et al, 1986b).…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…In these latter studies it was emphasized that the 4-carboxyglutamic acid domain was essential for activation by the thrombin-thrombomodulin complex, suggesting that interaction of the substrate with membrane is an essential prerequisite of the activation process. This was corroborated by the observation that an IgM lupus anticoagulant, with specificity directed towards anionic phospholipids, was able to neutralize the enhancing effect of phospholipids on purified thrombomodulin activity (Freyssinet et al, 1986b).…”
Section: Introductionmentioning
confidence: 64%
“…But in this case one would expect a competitive inhibition between protein C and fragment 1 for binding to phospholipids. In another study it was noticed that treatment of purified thrombomodulin with phospholipase C had no influence on its cofactor activity (Freyssinet et al, 1986b). Self-association of prothrombin fragment 1 and the formation of heterodimers between the vitamin K-dependent proteins (Harlos et al, 1987) have been recently demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…The first stage of the reaction, which contained 20 MI TBSG (TBS containing 1 mg/ml gelatin, pH 7.4), 10 TBS by centrifugation (8000 g, 1 min); resuspended in 50 1l TBS containing 5 mM CaCl2; mixed with 100 MI liposomes (1 mg/ml of total phospholipid in TBS); incubated 2 h on an orbital shaker at 370C; pelleted by centrifugation; washed two times with 1 ml of TBS; resuspended in 1 ml TBS containing 1 mg/ml gelatin, 1 mg/ml ovalbumin, and 10 mg/ml BSA; incubated 2 h at room temperature on a shaker; washed two times with 1 ml TBS; and resuspended in 500 IL TBS.`4C-PC incorporated into the liposomes was used to calculate the concentration of adsorbed liposomes. The phospholipid concentration in the final suspension was 50 pg/ml for both PS/PC and PE/PS/PC adsorbed liposomes.…”
Section: Thrombin Formation In Plasmamentioning
confidence: 99%
“…Indeed, both protein C activation (8)(9)(10) and activated protein C (APC)' anticoagulant activity (7,(11)(12)(13) have been shown to be partially inhibited by the lupus anticoagulants. Although antibodies to protein components of the pathway contribute in a small number of patients (see for instance reference 14), most patients appear to exhibit these protein C pathway inhibitory activities only in the presence of a membrane surface.…”
Section: Introductionmentioning
confidence: 99%
“…Proposed mechanisms include: direct endothelial damage [30]; inhibition of prostacyclin, and enhanced thromboxane A 2 production [31,32] and inhibition of endogenous anticoagulants such as thrombomodulin [33], protein C [34] and antithrombin III [35].…”
Section: Discussionmentioning
confidence: 99%